KERJASAMA INTERNASIONAL LEMBAGA PENDIDIKAN ISLAM - Dede Rubai Misbahul Alam; Nur Mawaddah Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research examines international cooperation between Islamic educational institutions as a strategy in responding to the challenges of globalisation in education. The development of scientific mobility, human resources, and cross-country collaboration requires Islamic educational institutions to increase their global quality and competitiveness without losing Islamic values. This research uses a qualitative approach with a library research method. Data was obtained from academic books, national and international journal articles, and relevant and up-to-date reports from international organizations. The data analysis was conducted through content analysis techniques to examine the concept, form, benefits, and challenges of international cooperation between Islamic educational institutions. The research results show that international cooperation, such as student and lecturer exchanges, research collaborations, curriculum development, and institutional networking, have a positive contribution to the improvement of academic quality and human resource capacity.